INOVASI MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN EFEKTIFITAS PROSES BELAJAR MENGAJAR - Muhammad Qomarul Munir; Muhammad Ainul Yaqin (LPPM STAI Muhammadiyah Probolinggo, 2026)
The effectiveness of the teaching and learning process remains a significant challenge in educational institutions, particularly in responding to the demands of digital transformation and the evolving needs of students. This study aims to analyze the principal’s managerial innovation in improving the effectiveness of the teaching and learning process at SMK Darul Hikmah Probolinggo, East Java. This research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation involving the principal, teachers, and students. The data were analyzed using the interactive model of data reduction, data display, and conclusion drawing, while data validity was ensured through source and method triangulation. The findings reveal four major forms of managerial innovation implemented by the principal: (1) data-based needs analysis as the foundation for decision-making, (2) digitalization of school administration through e-report systems and online management platforms, (3) periodic monitoring and evaluation of learning activities, and (4) strengthening link and match programs with business and industry sectors. These innovations contributed to improving learning management, teacher performance, and student engagement in the learning process. The study concludes that managerial innovation plays a strategic role in creating a more effective, adaptive, and sustainable learning environment that aligns with educational goals and labor market demands.